2020
DOI: 10.3390/ijerph17051537
|View full text |Cite
|
Sign up to set email alerts
|

Developing Youth Environmental Health Literacy and Civic Leadership through Community Air Monitoring in Imperial County, California

Abstract: With a rapidly changing climate, new leaders must be trained to understand and act on emerging environmental threats. In California’s Imperial Valley, a collaborative of community members, researchers, and scientists developed a community air monitoring network to provide local residents with better air quality information. To expand the reach of the project and to prepare the next generation of youth leaders we developed an internship program to increase environmental health literacy and civic leadership. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 15 publications
0
12
0
9
Order By: Relevance
“…Civic science contexts can help promote environmental health literacy among youths and create connections with environmental research and community action [ 39 ]. Both formal and informal environmental education makes meaningful participation in civic science possible [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Civic science contexts can help promote environmental health literacy among youths and create connections with environmental research and community action [ 39 ]. Both formal and informal environmental education makes meaningful participation in civic science possible [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that taking a community-based approach to air monitoring in this project increases local environmental health literacy, and provides direct benefits to community partners, such as engaging youth, and increased capacity and knowledge about air quality, data interpretation, and health impacts [36,37]. CCV led an extensive campaign to publicize the Network, presenting information during community events, meetings with school and other local officials, and interviews with news media.…”
Section: Discussionmentioning
confidence: 99%
“…Community gardens can also contribute to citizenship through gaining CK about the natural environment and learning skills in cultivating food (Bradley et al, 1999;Broaddus et al, 2015;Delia & Krasny, 2018;Dutta & Chandrasekharan, 2017;Horst et al, 2017;Madrigal et al, 2020). Numerous studies have shown the positive effects gardens have on connecting students to the land and helping students understand the importance of food systems and pro environmental attitudes.…”
Section: Community Gardens' Effect On Content Knowledgementioning
confidence: 99%